2005
DOI: 10.1002/cncr.21354
|View full text |Cite
|
Sign up to set email alerts
|

Age and comorbidity impact surgical therapy in older bladder carcinoma patients

Abstract: Body size and food properties account for much of the variation in the hard tissue morphology of the masticatory system whereas their influence on the soft tissue anatomy remains relatively understudied. Data on jaw adductor fiber architecture and experimentally determined ingested food size in a broad sample of 24 species of extant strepsirrhines allows us to evaluate several hypotheses about the influence of body size and diet on the masticatory muscles. Jaw adductor mass scales isometrically with body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(122 citation statements)
references
References 56 publications
5
106
0
11
Order By: Relevance
“…Prout and colleagues examined the SEER database and found that older patients with more comorbidity were less likely to undergo RC, even in the presence of invasive disease. 14 This tendency to defer definitive therapy may account for the association of higher comorbid disease with more advanced stages of bladder cancer observed in the present cohort.…”
Section: Discussionmentioning
confidence: 68%
“…Prout and colleagues examined the SEER database and found that older patients with more comorbidity were less likely to undergo RC, even in the presence of invasive disease. 14 This tendency to defer definitive therapy may account for the association of higher comorbid disease with more advanced stages of bladder cancer observed in the present cohort.…”
Section: Discussionmentioning
confidence: 68%
“…bleeding, instead of associated age-related illness 15 . Studies have suggested that co-morbidity and not age is the most important predictor of complications 15,16 . When the decision for a radical cystectomy is made, not the real but much better the ''biological'' age of the patient should be taken into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a comorbid condition may not only mask clinical signs of cancer and delay diagnosis, but may also preclude treatment options and even complicate the established cancer and/or effects of treatment (Piccirillo and Feinstein, 1996;Extermann, 2000;Prout et al, 2005;Hall, 2006). Several studies have found that bladder cancer is strongly associated with advanced age and tobacco smoking, each of which is associated with a distinct subset of additional comorbidities (Bjerregaard et al, 2006;Fisher et al, 2009).…”
Section: Commentmentioning
confidence: 99%